Recent Progress in 5-Hydroxymethylfurfural Catalytic Oxidation to 2,5-Furandicarboxylic Acid - Cai, Chiliu; Wang, Haiyong; Xin, Haosheng; Zhu, Changhui; Wang, Chenguang; Zhang, Qi; Liu, Qiying; Ma, Longlong (Current Organic Chemistry, 2021)
Biomass has attracted much attention because of its clean and renewable characteristics. The conversion of biomass into various fine chemicals and high value-added fuels is one of the important ways to solve the energy shortage and environmental pollution. 2,5-furan dicarboxylic acid (FDCA), a kind of important and promising new bio-based monomer, has attracted the attention of many researchers due to its wide applications in different industries. Therefore, many efforts have been made over various metal catalysts for FDCA production from this biomass-derived platform chemical, 5hydroxymethylfurfural (HMF). In this review, we introduced the reaction pathways of the aerobic oxidation of HMF to FDCA and summarized the recent progress of different catalysts and catalysis for HMF aerobic oxidation. Catalytic performance and reaction pathways are discussed in detail. Finally, conclusions and the remaining challenges are proposed and further prospects are presented in view of the technical aspects.
Keywords: catalysts